The Diagnostic Role of Dynamic Triphasic Spiral Computed Tomography in Liver Metastases - Arslanoğlu, Atilla; Sarı, Sebahattin (Fırat University, 2007)
Objectives: To evaluate the role of dynamic Triphasic Spiral Computed Tomography in liver metastases Material and Methods: Total 50 patients with focal liver lesions were evaluated with dynamic spiral CT. Liver was scanned three times in arterial, portal and equilibrium phases in order to determine enhancement patterns of the lesions. Hence, enhancement patterns of metastases and hemangiomas were evaluated separately. Results: We detected uniformly hypodense or peripherally enhanced hypodense appearances at arterial and portal phases in 96.6% of metastatic cases. While same pattern was observed in arterial and portal phases of 93.7% of hemangiomas, delayed phases revealed totally hyperdense or isodense appearance with central opacification. Hypervascular metastasis of pancreatic islet cell carcinoma, known as a hypervascular tumor itself, were visualized only in the arterial phase as hyperdens foci. Conclusion: Triphasic dynamic spiral CT is decided to be a useful technique in patients with focal liver lesions, since it provides valuable information about the nature and differentiation of focal liver lesions as well as their relations with the neighboring vascular structures. ©2007, Firat University, Medical Faculty

Giriş: Karaciğer metastazlarında dinamik spiral bilgisayarlı tomografinin rolünü incelemektir. Gereç ve Yöntem: Karaciğerde fokal kitle lezyonu olan toplam 50 hasta dinamik trifazik spiral BT ile incelenmiştir. Karaciğer lezyonların boyanma paternlerini saptamak için arteriel, portal ve geç fazda ayrı ayrı 3 kez taranmıştır. Böylece metastaz ve hemanjiomların boyanma karakteristiklerini ayrı ayrı değerlendirmek mümkün oldu. Bulgular: Bu çalışmada, karaciğerdeki metastatik lezyonların %96.6'nın arteriyel ve portal fazda, üniform hipodens veya periferal hiperdens boyanma paterni gösterdiğini saptadık. Ancak hemanjiom olgularımızda da %93.7 oranında arteriyel ve portal fazda aynı boyanma özelliği gözlenmekte, fakat geç fazda lezyonlar total hiperdens veya total izodens hale gelmekte veya santral opasifikasyon artmaktaydı. Hipervasküler bir tümör olarak bilinen pankreas islet cell karsinomlu olgumuzda hipervasküler metastazlar sadece arteriyel fazda hiperdens olarak izlendi. Sonuç: Trifazik dinamik spiral BT incelemesi karaciğerdeki fokal lezyonların ayırıcı tanısında önemli bilgiler vermesi ve lezyonların komşu vasküler yapılarla olan ilişkisini değerlendirmesi nedeniyle, klinik kullanımda karaciğerde fokal lezyonları olan hastalarda seçilebilecek değerli bir yöntem olduğu kanaatine varılmıştır. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Karaciğer Metastazlarında Dinamik Spiral Bilgisayarlı Tomografinin Diagnostik Rolü